2011
DOI: 10.1371/journal.pgen.1002217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Toxin/Immunity Genes Linked to Contact-Dependent Growth Inhibition (CDI) and Rearrangement Hotspot (Rhs) Systems

Abstract: Bacterial contact-dependent growth inhibition (CDI) is mediated by the CdiA/CdiB family of two-partner secretion proteins. Each CdiA protein exhibits a distinct growth inhibition activity, which resides in the polymorphic C-terminal region (CdiA-CT). CDI+ cells also express unique CdiI immunity proteins that specifically block the activity of cognate CdiA-CT, thereby protecting the cell from autoinhibition. Here we show that many CDI systems contain multiple cdiA gene fragments that encode CdiA-CT sequences. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
270
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(275 citation statements)
references
References 41 publications
3
270
0
Order By: Relevance
“…The CdiA-CT II Bp1026b /CdiI II Bp1026b proteins are derived from the CDI locus on chromosome II of Bp1026b (5), and the CdiA-CT o11 EC869 /CdiI o11 EC869 complex is encoded by the 11th "orphan" (o11) module of E. coli EC869. Orphan cdiA-CT/cdiI modules are toxin/immunity gene pairs that have been displaced from fulllength cdiA genes (8). Tandem arrays of these modules are often associated with CDI systems and are thought to represent reservoirs of toxin/immunity diversity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The CdiA-CT II Bp1026b /CdiI II Bp1026b proteins are derived from the CDI locus on chromosome II of Bp1026b (5), and the CdiA-CT o11 EC869 /CdiI o11 EC869 complex is encoded by the 11th "orphan" (o11) module of E. coli EC869. Orphan cdiA-CT/cdiI modules are toxin/immunity gene pairs that have been displaced from fulllength cdiA genes (8). Tandem arrays of these modules are often associated with CDI systems and are thought to represent reservoirs of toxin/immunity diversity.…”
Section: Resultsmentioning
confidence: 99%
“…2A) is required for DNase activity. This toxin-encoding sequence could not be cloned in the absence of the cognate immunity gene; therefore, we used controlled proteolysis of CdiI o11 EC869 to activate the CdiA-CT o11 EC869 toxin inside E. coli cells (8,12). Briefly, the C terminus of CdiI o11 EC869 was tagged with the ssrA(DAS) peptide, which targets the immunity protein for degradation by the ClpXP protease, thereby liberating the CdiA-CT to exert its toxic activity.…”
Section: Cdia-ct O11mentioning
confidence: 99%
See 1 more Smart Citation
“…Although CysK is critical for CdiA-CT EC536 nuclease activity, related toxins from Gram-positive bacteria probably do not require extrinsic activation because purified Tox28 domain from R. lactaris has tRNase activity in vitro. Ntox28 domains are typically found at the C terminus of proteins that mediate interbacterial competition (4,(29)(30)(31). For example, the R. lactaris Tox28 Rlac domain is part of a larger EC536 were treated with formaldehyde, and cross-linked nucleoprotein complexes were purified by Ni 2+ -affinity chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…We disrupted sciW, rhs1, and rhs2 and found that disruption of rhs2 produced the same defect in systemic dissemination in mice as disruption of core T6SS genes and the entire SPI-6 locus (19). This Rhs element is located with sciX in a bicistronic operon and may also function as a toxin/immunity gene pair participating in contact-dependent growth inhibition (40).…”
Section: Figmentioning
confidence: 97%